Reformed - Weinberger, Justin (Scholastic Press, 2017)
Ian Hart is framed for pranking a new student and is sent to bully reform school with his friends Ash and Alva. There the pranks are rougher, the girls meaner, and the teachers unpredictable. It will take everything the friends have to make it into middle school alive.